Exploring pollinizers for enhancing productivity in ’Alphonso’ mango (Mangifera indica) - SHINDE, A K; WAGHMARE, G M; PATIL, B P (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during 1998-99 and 1999-2000 to explore pollinizers for increasing productivity in mango (Mangifera indica L.). Manual pollination with different pollinizer varieties under test indicated that ’Tomy Atkins’, followed by ’Kesar’, ’Goa Mankur’ and ’Ratna’ increased fruits set by 16 to 17%,8 to 14%, 10 to 13% and 10 to 13% respectively during 1998-99 and 1999-2000. Pollinizer varieties ’Pairi’. ’Ostin’ and ’Maya’ proved the next promising pollen donors. shuwing fruit retention 10%. The other varieties under test were poor pollinizers with 4 to 7.5% retention. Flowering synchrony evaluation revealed that ’Kesar’, ’Goa Mankur’, ’Vellai Kolumban’, ’Sindhu’, ’Ratna’ and ’Panchadarakalasha’ had synchronized tlowering with’ Alphonso’. But ’Kesar’, ’Goa Mankur’ and ’Ratna’ proved compatible as successful pollinizers having acceptable effect of fruit quality. Field verification of the 2 pollinizer varieties (Kesar’ and ’Goa Mankur’) planted in ’Alphonso’ garden showed significant increase in yield (84%) of ’Alphonso’.